Cliff-hanger - Skurzynski, Gloria; Ferguson, Alane (Washington, D.C. : National Geographic Society, 2007)
Twelve-year-old Jack and his younger sister visit Mesa Verde National Park, where they delve into the park's history while gradually uncovering the mysterious past of their family's teenage foster child Lucky.
670
670
Accelerated Reader AR
Keywords: Foster home care -- Fiction; National parks and reserves -- Fiction; Mystery and detective stories; Mesa Verde National Park (Colo.) -- Fiction